INTERNATIONAL MYOPIA INSTITUTE – A GLOBAL PERSPECTIVE - Jong, Monica (International Journal of Allied Health Sciences, 2021)
This talk will provide an overview of the International Myopia and its work in the advocacy of myopia and high myopia as a public health issue. The IMI published landmark white papers in 2019 providing the first evidence-based guidance to practitioners, researchers and policy makers, with a mission to prevent vision impairment and blindness associated with higher levels of myopia. The future directions will also be presented.